Luís Fróis’s História de Japam: aims and methods - Takamura, JA (2019)
The focus of the thesis is the work of the Portuguese Jesuit missionary Luís Fróis (1532-97). It refutes the view of the historiography that has considered his magnum opus the História de Japam, produced between 1584-93, as bona fide and as one of the most reliable sources on the basis that he was often either a protagonist or an eyewitness of the events that he relates. As it will be shown in this work, Fróis is selective in the manner in which he deletes, adds or avoids facts, or simply creates narratives purposefully composing an edifying account. Fróis takes the opportunity to put forward his view of the mission by fusing history and sacred rhetoric, such as the use of rhetorical devices, to elevate the volume of the message that had previously been recorded in the Jesuits’ correspondence, or sometimes silencing it completely. For this reason, I argue that Fróis should be considered not only the first historian of the mission, but also the first editor of the history of the Japanese mission by writers who took part in the evangelisation of this country. Through the reading of Fróis’s História there is an underlying theme of the ‘opposite cultures’ between Japan and Europe. This is not so much born out of a fascination with a very different culture, as some historians have alluded, but my readings are rather that it serves in justifying the Jesuit’s controversial method of accommodation implemented at the time in the archipelago. It also signals to a belief of the incommensurability between these cultures, reflecting on a decrease in the dialogue and the beginning of an increase in the distancing between these societies.